THE ROLE OF LEADERSHIP OF ISLAMIC HIGHER EDUCATION LEADERS IN INDONESIA IN IMPROVING THE QUALITY OF ARABIC LANGUAGE EDUCATION PROGRAMS - Satriadi, Budi; Attruk, Muhammad Fariq Heemal (Four Son Scholarship, 2026)
Leadership in higher education is widely recognized as a strategic factor influencing institutional governance, academic culture, and program quality; however, the relationship between leadership in Islamic Higher Education Institutions (PTKI) in Indonesia and the quality of Arabic Language Education Programs (PBA) has not yet been conceptually synthesized within a unified analytical framework. This study aims to develop a conceptual understanding of how institutional leadership relates to PBA quality through governance mechanisms and academic policy. Using a Narrative Literature Review approach, this study synthesizes empirical and theoretical publications from 2015 to 2025, focusing on leadership models in higher education, leadership within Islamic higher education in Indonesia, and key quality indicators of Arabic Language Education Programs, including curriculum aligned with Outcome-Based Education and the national qualifications framework, faculty professionalism, the development of bi’ah lughawiyah (Arabic language environment), and internal quality assurance systems linked to accreditation. The findings indicate that while no single study directly examines the relationship between PTKI leadership and PBA quality, consistent patterns suggest that strategic leadership is associated with curriculum reform and organizational change, transformational leadership with faculty commitment and academic culture, innovative leadership with institutional adaptability, and managerial capacity with the sustainability of quality assurance cycles. This study proposes a multi-level leadership model (rector–dean–head of study program) that conceptualizes PBA quality as the result of coordinated policy integration, governance structures, and institutional culture, highlighting the systemic and mediating role of leadership in shaping program quality within Islamic higher education in Indonesia